2018
DOI: 10.1111/are.13741
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and nutritional composition ofSepia pharaonisunder artificial culturing conditions

Abstract: This study investigated the growth performance and nutritional composition of scale artificially cultured cuttlefish Sepia pharaonis. Juveniles were cultured in an open-culturing cement pool system for 120 days. The body weight increased from 10.21 AE 1.44 g to 570.71 AE 126.32 g from 50 days old to 170 days old, and the average growth rate was 4.67%. The proximate, amino acid and fatty acid compositions of S. pharaonis muscles were analysed every 40 days to compare the quality. The cultured S. pharaonis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Second generation (F 2 ) fertilized eggs of S. pharaonis were obtained from brood stock maintained at the Lai Fa Aquaculture Co. Ltd research facility (29°59′N, 121°99′E), Zhejiang Province, China. After hatching, animals were reared according to the latest culture methods described in Jiang et al (2018). Newly hatched juveniles were fed with enriched live brine shrimp (Artemia nauplii) and live mysids (Hyperacanthomysis brevirostris) within the first 3 days post-hatching, followed with live mysids twice a day (at 08:00 and 16:00 hours) ad libitum, ensuring that the cuttlefish had sufficient food supply at all times.…”
Section: Animalsmentioning
confidence: 99%
“…Second generation (F 2 ) fertilized eggs of S. pharaonis were obtained from brood stock maintained at the Lai Fa Aquaculture Co. Ltd research facility (29°59′N, 121°99′E), Zhejiang Province, China. After hatching, animals were reared according to the latest culture methods described in Jiang et al (2018). Newly hatched juveniles were fed with enriched live brine shrimp (Artemia nauplii) and live mysids (Hyperacanthomysis brevirostris) within the first 3 days post-hatching, followed with live mysids twice a day (at 08:00 and 16:00 hours) ad libitum, ensuring that the cuttlefish had sufficient food supply at all times.…”
Section: Animalsmentioning
confidence: 99%
“…Experiments were conducted at the Lai Fa Aquaculture Co., Ltd. (29° 59′ N, 121° 99′ E) (Zhejiang Province, China), which specializes in aquatic technology research and application development. Posthatching, cuttlefish were reared in a cement pond (7.8 m × 3.8 m × 1.6 m, length × width × depth; area, 30 m 2 ), as described for the species by Jiang et al (2018). In short, newly hatched juveniles were fed enriched live rotifers ( Artemia nauplii ) the first 3 days posthatching and then live mysids ( Hyperacanthomysis brevirostris ) twice a day (8:00 and 16:00) ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…We observed that the pigmentation stage of embryonic development is capable of releasing ink when manipulated vigorously. Besides, cuttlefish release ink during rearing, e.g., weaning, competition for food, mating, and rapid changes in temperature and salinity (Le et al, 2014; Lee et al, 2016; Jiang et al, 2018). Furthermore, overrelease of ink results in the individual’s death.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Jiang et al. (2018) and Correia et al. (2005) outlined the relationship between the size and stocking density of cultured cuttlefish, indicating that the culture density needs to be reduced as the size of cuttlefish increases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these two species, S. pharaonis and S. officinalis, are closely relatives, experimental studies and breeding practices found that they share many common characteristics, such as fast growth rates, short life spans and adaptable feeding habits; therefore, they have been proposed as an excellent candidate for large‐scale artificial culture (Barord et al., 2010; Jiang et al., 2018; Sykes, Domingues, Correia et al., 2006; Sykes, et al., 2009; Vidal et al., 2014). S. pharaonis was raised to an age of 170 days, fed live mysids ( Hyperacanthomysis brevirostris ), frozen shrimp ( Penaeus vannamei ) and fish ( Larimichthys polyactis ), with a yields of up to 5,000 individuals and weights of 570.71 ± 126.32 g (Jiang et al., 2018). Consequently, frozen food is necessary to achieve large‐scale farming, as it is a good way to ensure increased and continuous production.…”
Section: Introductionmentioning
confidence: 99%